The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1180/0009855043940142
|View full text |Cite
|
Sign up to set email alerts
|

On the destruction of kaolinite and gibbsite by phenylphosphonic, phenylphosphinic and phenylarsonic acids: evidence for the formation of new Al compounds

Abstract: Kaolinite and synthetic γ-Al(OH)3 (gibbsite or hydrargillite) were reacted with phenylphosphonic, phenylphosphinic and 2-nitrophenol-4-arsonic acids. The products were studied by powder X-ray diffraction, transmission electron microscopy/selected area electron diffraction/ energy dispersive X-ray/Fourier transform infrared and simultaneous thermogravimetric/differential thermal analysis. The acids were not intercalated but, instead, easily destroyed the structure of the minerals. Lamellar Al phenylphosphonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the spectrum of PPA/C 10 O-HLaNb, a broad signal is observed at 13 ppm, whereas broad signals are present at 28-30 ppm in the spectra of APA/C 10 O-HLaNb. The solid-state 31 P MAS NMR spectra of PPA and APA molecules were also measured. The spectrum of PPA displayed a signal at 22 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the spectrum of PPA/C 10 O-HLaNb, a broad signal is observed at 13 ppm, whereas broad signals are present at 28-30 ppm in the spectra of APA/C 10 O-HLaNb. The solid-state 31 P MAS NMR spectra of PPA and APA molecules were also measured. The spectrum of PPA displayed a signal at 22 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Solid-state 13 C and 31 P nuclear magnetic resonance (NMR) spectroscopy was performed with a JEOL CMX-400 (9.4 T) spectrometer at 100.54 and 161.84 MHz, respectively. Solid-state 13 C NMR spectra were obtained with cross-polarization (CP) and magic angle spinning (MAS) techniques (pulse delay, 5s; contact time, 1.5 s; spinning rate, 8 kHz), while solid-state 31 P NMR spectra were obtained with a MAS technique only (pulse delay, 20 s; pulse angle, 90°; spinning rate, 8 kHz). Inductively coupled plasma emission spectrometry was performed with a Thermo Jarrel Ash ICAP-574 II instrument after dissolving the sample (about 1.8 mg) in a mixture of 5 mL of conc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] A possible alternative reaction path for imogolite is the formation of bulk aluminum phosphonates. It is already known for the intercalation of gibbsite and kaolinite with phenylphosphonic acid (PPA) 23 , the modification of aluminum oxide by ODPA 24 and PPA 4 , and the modification of germanium imogolite by ODPA. 19 Nonetheless, it was shown that choosing favorable conditions prevents the bulk phosphonate formation and enables grafting of alumina by octylphosphonic acid.…”
Section: Introductionmentioning
confidence: 99%